ANTHROPOMETRIC ASSESSMENT OF NUTRITIONAL STATUS AMONG COLLEGE WOMEN OF MIDNAPORE, WEST BENGAL, INDIA: Life Sciences-Biological Anthropology - MANDAL, SUMANA; SINHA, NIRMALYA KUMAR; SAMANTA, PRADIP; DAS, SUBAL; BOSE, KAUSHIK (International Journal of Life Science and Pharma Research, 2011)
A woman’s nutritional status has important implications for her health as well as the health of her children. The present cross-sectional study was undertaken to determine the overall prevalence of undernutrition among young adult women of Raja N. L. Khan Women’s College, Midnapore, West Bengal, India. Our study measured data on height and weight of adults aged 18-20 years. A total of 491 females were measured. One commonly used indicator i.e., body mass index (BMI; kg/m2), was used to evaluate the nutritional status of the subjects. Based on BMI, chronic energy deficiency (CED) was used as a measure of undernutrition. The mean (SD) BMI of the subjects was 20.05 kg/m2 (SD = 2.63). Results revealed that there was a significant (F = 4.085***, p < 0.001) increasing age trend in mean BMI. The overall age combined prevalence of CED was 28.3 %. Overall, only 4.5 % belonged to the overweight category. A significant (chi-square = 31.439; p < 0.001) age relationship existed in the prevalence of CED. According to the WHO classification of low BMI, it is clear that studied college girls of Midnapore, India are in serious situation for all ages and the youngest (18 years) among them are experiencing the most serious situation (32.7 %) with respect to their health and nutritional status. Overall prevalence of CED was (28.3 %). Conditions of the young women’s were more severe and this severity decreases with increasing age of these women’s. Results have been compared with recent reports from 18 states of India.